Time-frequency forecast of the equity premium - Gonçalo Faria; Fabio Verona (Bank of Finland, 2020)
Any time series can be decomposed into cyclical components fluctuating at different frequencies. Accordingly, in this paper we propose a method to forecast the stock market's equity premium which exploits the frequency relationship between the equity premium and several predictor variables. We evaluate a large set of models and find that, by selecting the relevant frequencies for equity premium forecasting, this method significantly improves in both statistical and economic sense upon standard time series forecasting methods. This improvement is robust regardless of the predictor used, the out-of-sample period considered, and the frequency of the data used.
URN:NBN:fi:bof-202004282094
Keywords: C58; G11; G17; 330; time-frequency forecast; equity premium; multiresolution analysis